Adaptive Corporate Governance Theory: A Dynamic Framework for the 21st Century - AYIBAM, Joanna Nyaposowo (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2025)
Corporate governance theories have struggled to keep pace with rapid technological disruption, evolving stakeholder expectations, and geopolitical volatility. This paper proposes Adaptive Corporate Governance Theory (ACGT), a novel framework arguing that governance structures must be context-dependent, dynamic, and experimentally validated to remain effective. Unlike static models (e.g., Agency Theory, Stakeholder Theory), ACGT integrates real-time feedback loops, trigger-based adaptation mechanisms, and regulatory sandboxing to address gaps in traditional governance paradigms. Drawing on interdisciplinary research from corporate law, organizational behavior, and complexity economics, the paper demonstrates how ACGT’s core principles—context-dependent governance, stakeholder-sensitive decision-making, dynamic fiduciary duties, and experimental legal frameworks—can resolve tensions between shareholder primacy and multi-stakeholder demands. A comparative analysis of governance failures (e.g., crypto exchange collapses, ESG greenwashing scandals) illustrates ACGT’s predictive and prescriptive advantages. The paper concludes with a roadmap for operationalizing ACGT, including proposed amendments to corporate charters, fiduciary standards, and regulatory sandbox policies. By prioritizing adaptability over rigidity, ACGT offers a timely solution for governing firms in an era of AI, climate transition, and decentralized organizations.